The Balancing Act between Touism and the Environment in Maasai Mara - Case Study: Mara Serena Safari Lodge - Bid, Hema (2006)
This dissertation aims to analyse the balancing act between tourism and the environment in the Maasai Mara National Reserve, and assess its impacts in relation to sustainable tourism. Furthermore, the researcher will analyse how tourism wildlife laws have changed from 1930 to present, and the evolution of the relationship between tourists, local people (Maasai) and wildlife in the area. The main objectives of this dissertation are to make different stakeholders in Maasai Mara aware of: - How Maasai Mara's tourist attractions can be managed and utilised on a socially, environmentally and ecologically sustainable basis, using Mara Serena Safari Lodge as an example. - How much of the revenue from tourism trickles down to local people at the grassroots level. - How the awareness in sustainable development and the participation of the local community will ensure a good quality eco-friendly tourism product.